Predicting 28-day mortality for patients with acute anterior circulation large vessel occlusion stroke following endovascular treatment in neurology intensive care units - Qin, Wenjing; Xiao, Chengcheng; Yang, Jing; Hu, Mei; Chang, Liying; Zhu, Yanhan (Frontiers in Neurology, 2025)
BackgroundThe clinical utility of the National Institutes of Health Stroke Scale, Glasgow Coma Scale, and modified Rankin Scale scores in predicting prognosis is well established. However, whether the Acute Physiology and Chronic Health Evaluation System II (APACHE II) score can predict mortality in patients with large vessel occlusion stroke (LVOS) admitted to the neurology intensive care unit (NICU) following endovascular treatment (EVT) remains unclear. This study aims to evaluate the ability of the APACHE II score to predict mortality in post-EVT LVOS patients admitted to the NICU.MethodsThis retrospective cohort study enrolled 93 consecutive patients (65 males; mean age, 68.0 years) with acute anterior circulation LVOS who underwent EVT. Patients were categorized into survival and death groups based on their 28-day post-EVT survival status. APACHE II scores of the two groups were compared. Receiver operating characteristic (ROC) curve analysis was employed to assess the sensitivity, specificity, and optimal threshold of APACHE II scores in predicting mortality. Model calibration was assessed using the Hosmer-Lemeshow goodness-of-fit test. Multivariable logistic regression was performed to estimate odds ratios (ORs) for mortality prediction.ResultsOf the 93 enrolled patients, 74 (79.6%) survived and 19 (20.4%) died within 28 days. The death group had significantly higher APACHE II scores than the survival group [(21.84 ± 4.10) points vs. (13.05 ± 5.54) points, p < 0.001]. ROC analysis revealed excellent discriminative capacity (AUC 0.912, 95% CI 0.850–0.973), with an optimal threshold of 16.5 points (sensitivity 94.7%, specificity 75.7%). The mortality rate was 1.8% for patients with APACHE II scores <16.5 points and 50.0% for those with APACHE II scores ≥16.5 points. The model demonstrated good calibration (p = 0.878). Further, multivariable analysis confirmed both APACHE II scores (OR = 1.239, 95% CI 1.029–1.491, p = 0. 023) and cerebral hernia (OR = 11.404, 95% CI 1.507–86.314, p = 0. 018) as independent predictors.ConclusionAPACHE II score assessed within 24 h post-EVT provides robust prediction of 28-day mortality in acute anterior circulation LVOS patients admitted to the NICU.